Clinical Characteristics of Target Organ Damage in Primary Aldosteronism with or without Metabolic Syndrome - Xiaona Bu; Fang Sun; Hexuan Zhang; Xiaoli Liu; Zhigang Zhao; Hongbo He; Yingsha Li; Zhencheng Yan; Zhiming Zhu (Journal of Diabetes Research)
The aim of this study is to investigate the prevalence of metabolic disorders in patients with primary aldosteronism (PA) and target organ damage (TOD) in different subtypes of patients with PA with or without metabolic syndrome (MS). Patients with PA were screened out from those with secondary hypertension and then subtyped via adrenal venous sampling (AVS). Baseline clinical characteristics (blood pressure, blood glucose, abdominal circumference, and lipid profile) were collected for the diagnosis of MS. Organ damage was evaluated according to cardiac and carotid ultrasound and urine microalbumin measurements. In all 261 patients with PA, 113 patients had concomitant MS and experienced more severe cardiac hypertrophy and increased intima-media thickness (IMT). The incidence of MS and diabetes mellitus (DM) had no statistic difference between the two groups, moreover, the rates of TOD were not different except microalbuminuria. However, metabolic disorders caused more remarkable TOD in PA patients with unilateral hypersecretion. It showed that cardiac hypertrophy was associated with obesity while microalbuminuria was related to plasma aldosterone concentration (PAC) in PA patients. In this retrospective study, our findings suggest that the effect of metabolic disorders on organ damage is more remarkable in patients with unilateral PA.